Binder-free MWW structure molecular sieve catalyst as well as preparation method and application thereof

Through the preparation method of MWW structure molecular sieve catalyst without binder, the problem of reducing catalyst activity caused by carbon deposits in by-products in cyclohexylbenzene production is solved, and a high selectivity and long-life catalyst is achieved, and the defect of binder blocking the pores is avoided.

CN119702060AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311272742.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

In the prior art, macromolecular by-products are easily generated during the production process of cyclohexylbenzene, resulting in a reduced catalyst activity and short service life. Commonly used binders will block the molecular sieve pores and affect the diffusion performance.

Method used

Using a binder-free MWW structure molecular sieve catalyst, a high specific surface area and ultra-thin layer MWW structure molecular sieve catalyst is prepared by fully uniformly mixing the silicon source and aluminum source raw materials in the solid phase and crystallizing it in water vapor or organic structure guide agent. This method prevents the problem of the adhesive from clogging the pores by introducing a binder to control the crystal thickness and specific surface area.

Benefits of technology

The selectivity of cyclohexylbenzene and the service life of the catalyst are significantly improved, while the external specific surface area and specific surface area of ​​the catalyst are increased, and the diffusion performance of the reaction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702060A_ABST
    Figure CN119702060A_ABST
Patent Text Reader

Abstract

The invention discloses a binderless MWW structure molecular sieve catalyst as well as a preparation method and application thereof. The outer specific surface area of the catalyst is more than 200m < 2 > / g, and the crystal thickness of the catalyst is less than 10nm. The preparation method of the catalyst comprises the following steps: mixing and molding MWW molecular sieve raw powder, a binder and an alkali source to obtain a precursor; mixing the precursor with cyclohexane and low-carbon alcohol, and separating; mixing a solid obtained by separation with a template agent and water, performing hydrothermal crystallization, and performing first roasting; and carrying out ammonium exchange and secondary roasting on the first roasted product to obtain the MWW structure molecular sieve catalyst. The catalyst provided by the invention is used in a reaction for synthesizing cyclohexylbenzene through alkylation of cyclohexene and benzene, and has higher product selectivity and reaction stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of MWW structured molecular sieve catalysts, and in particular relates to a binder-free MWW structured molecular sieve catalyst and a preparation method and application thereof. Background Art

[0002] The molecular formula of cyclohexylbenzene (CHB) is C 12 H 16 . The purpose of cyclohexylbenzene is to produce phenol and cyclohexanone through oxidation and acid decomposition reactions. At present, the production process of cyclohexylbenzene mainly includes hydrogenation alkylation of benzene, selective hydrogenation of biphenyl and FC alkylation of benzene and cyclohexene. Among them, the FC alkylation of benzene and cyclohexene is to prepare cyclohexylbenzene with benzene and cyclohexene as raw materials under the action of acidic catalysts such as Lewis acid, ionic liquid and zeolite molecular sieve. Among them, zeolite molecular sieve, as a solid acid catalyst, can reduce separation costs while producing green, and has great industrial application prospects. The molecular size of cyclohexylbenzene is relatively large, and it is easy to generate dicyclohexylbenzene by-products with extremely large molecular sizes during the synthesis process. It is difficult to diffuse and is easy to deposit carbon at the pores of the molecular sieve, blocking the pores, causing the activity of the catalyst to be greatly reduced and the service life to be greatly reduced. Therefore, it is crucial to increase the diffusibility of the molecular sieve and have a larger external specific surface area.

[0003] MWW molecular sieve is a sheet-like molecular sieve, whose pore system includes two sets of unconnected ten-membered ring pores (one of which contains a twelve-membered ring cylindrical supercage) and a bowl-shaped twelve-membered ring semi-supercage located on the outer surface of the crystal. Its outer surface has an open bowl-shaped semi-supercage structure. Compared with other molecular sieves, it has a stronger benzene adsorption capacity and is conducive to the diffusion of reaction molecules, making it an ideal alkylation catalytic material.

[0004] During industrial production, molecular sieve powder is usually bonded and formed with a binder, which generally accounts for about 40% of the total mass of the catalyst. However, commonly used catalyst binders are generally inert components, such as alumina, silica and kaolin, which will block the pores of the molecular sieve, weaken its adsorption performance, increase diffusion resistance, affect the diffusion performance of the reaction, and lead to a decrease in reaction activity and selectivity. Binderless molecular sieves are made by fully and evenly mixing raw materials such as silicon source and aluminum source in a certain ratio in the solid phase, and then crystallizing them in water vapor or organic structure directing agents, so that the binder molecules grow crystals under solid phase conditions. Due to the absence of a binder, it has a larger specific surface area and has better performance in adsorption separation and catalytic reactions.

[0005] CN114162833A discloses a method for preparing a thin layer of MCM-22 molecular sieve microspheres with a microporous and mesoporous structure. The method forms a "desert rose" morphology by adding a second template, and the catalyst prepared by the method can be used in the liquid phase alkylation reaction of benzene and ethylene. However, the molecular sieve microspheres obtained by the method are 1-2 microns, and a binder component still needs to be added when the catalyst is used, thereby causing a pore blocking effect on the molecular sieve, increasing diffusion resistance, and macromolecules such as cyclohexylbenzene and dicyclohexylbenzene are not easy to diffuse, resulting in low product selectivity and a short catalyst service life.

[0006] CN107512727A discloses a method for preparing a binder-free MWW structure molecular sieve. The method crystallizes the binder into MCM-22 molecular sieve by gas-solid phase crystallization, solves the problems of long crystallization time and incomplete crystallization, and has good catalytic activity in the liquid phase alkylation reaction of benzene and ethylene. When the molecular sieve is used as a catalyst in the FC alkylation reaction of benzene and cyclohexene, the byproduct dicyclohexylbenzene will quickly deposit carbon at the orifice, resulting in a short catalyst service life. Summary of the invention

[0007] In order to solve the above technical problems, the object of the present invention is to provide a binderless MWW structure molecular sieve catalyst and its preparation method and application. The MWW structure molecular sieve catalyst is a high specific surface area, ultra-thin layer binderless MWW structure molecular sieve catalyst. The catalyst is used in the reaction of cyclohexene and benzene alkylation to synthesize cyclohexylbenzene, and has higher product selectivity and reaction stability.

[0008] The first aspect of the present invention provides a binder-free MWW structure molecular sieve catalyst, wherein the external specific surface area of ​​the catalyst is 200m 2 / g or more, preferably 200 to 280 m 2 / g, the crystal thickness of the catalyst is less than 10nm, preferably 3-8nm.

[0009] According to the present invention, the SiO2 / Al2O3 molar ratio of the binder-free MWW structured molecular sieve catalyst is 20-80.

[0010] According to the present invention, the specific surface area of ​​the binder-free MWW structured molecular sieve catalyst is 400 to 600 m 2 / g.

[0011] According to the present invention, when preparing the binder-free MWW molecular sieve catalyst, the binder introduced is in an oxide-based mass ratio to the MWW molecular sieve raw powder in a dry basis of 0.5 to 12:1, preferably 1 to 9:1. The binder is preferably a silicon-containing binder and an aluminum-containing binder.

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned MWW structured molecular sieve catalyst, comprising:

[0013] (1) Mixing MWW molecular sieve raw powder, a binder, and an alkali source to obtain a precursor;

[0014] (2) mixing the precursor of step (1) with cyclohexane and low-carbon alcohol, and separating them;

[0015] (3) mixing the solid separated in step (2) with a template and water, hydrothermally crystallizing the mixture, and performing a first calcination;

[0016] (4) subjecting the calcined product obtained in step (3) to ammonium exchange and a second calcination to obtain the MWW structured molecular sieve catalyst.

[0017] According to the present invention, in step (1), the properties of the MWW molecular sieve raw powder are: SiO2 / Al2O3 molar ratio is 25-100. The specific surface area is 350-550m 2 The crystal thickness of the MWW molecular sieve raw powder is less than 15 nm, preferably 3 to 10 nm.

[0018] According to the present invention, in step (1), the molding is preferably extrusion molding. In step (1), during the mixing and molding of the MWW molecular sieve raw powder, the binder, and the alkali source, a molding aid such as a pore former, a peptizing acid, etc. may be added. The pore former includes at least one of sesbania powder and methyl cellulose. The peptizing acid is preferably a nitric acid solution. The mass concentration of the nitric acid solution is 0.5% to 5%, preferably 1% to 3%.

[0019] According to the present invention, in step (1), the binder is preferably a silicon-containing binder and an aluminum-containing binder. The silicon-containing binder includes at least one of silica sol, white carbon black and silicon powder. The aluminum-containing binder is an inorganic aluminum salt. The aluminum-containing binder includes at least one of sodium aluminate, aluminum sulfate and aluminum nitrate.

[0020] According to the present invention, in step (1), the alkali source is a base having an alkali metal and / or an alkaline earth metal as a cation; more preferably, the alkali source includes at least one of sodium hydroxide, potassium hydroxide and barium hydroxide.

[0021] According to the present invention, preferably, in step (1), the mass ratio of MWW molecular sieve raw powder, binder and alkali source is 1:0.5-12:0.02-0.2, preferably 1:1-9:0.05-0.1. The MWW molecular sieve raw powder is calculated on a dry basis of the MWW molecular sieve, and the binder is calculated on an oxide basis.

[0022] According to the present invention, in step (1), the binder is preferably a silicon-containing binder and an aluminum-containing binder. The mass ratio of the MWW molecular sieve raw powder, the silicon-containing binder, the aluminum-containing binder, and the alkali source is 1: 0.5-10: 0.01-2: 0.02-0.2, preferably 1: 1-8: 0.05-1: 0.05-0.1. Among them, the MWW molecular sieve raw powder is calculated on a dry basis of the MWW molecular sieve, the silicon-containing binder is calculated on a SiO2 basis, and the aluminum-containing binder is calculated on a Al2O3 basis.

[0023] According to the present invention, preferably, in step (1), the mass ratio of MWW molecular sieve raw powder, pore former and peptizing acid is 1: 0.01-0.1: 0.2-3, preferably 1: 0.01-0.05: 0.5-2. The MWW molecular sieve raw powder is calculated on a dry basis of the MWW molecular sieve.

[0024] According to the present invention, in step (2), the low-carbon alcohol is selected from at least one of alcohols below C6, preferably at least one of methanol, ethanol and isopropanol.

[0025] According to the present invention, in step (2), the mass ratio of the precursor to cyclohexane and low-carbon alcohol is 1:0.5-2:0.5-5; preferably 1:0.7-1.5:1-3.

[0026] According to the present invention, in step (2), the treatment temperature is 40 to 90° C., and the treatment time is 1 to 5 hours. The treatment method is to stand in a mixed solution of cyclohexane and ethanol. The separation can be a conventional solid-liquid separation method.

[0027] According to the present invention, in step (3), the template agent includes at least one of hexamethyleneimine, piperidine, cyclohexylamine, aniline and homopiperazine.

[0028] According to the present invention, in step (3), the mass ratio of the solid separated in step (2) to the template and water is 1:0.3-1.5:0.5-4, preferably 1:0.8-1.5:1-3.

[0029] According to the present invention, in step (3), the conditions of the hydrothermal crystallization include: a crystallization temperature of 140 to 170°C, preferably 150 to 160°C; a crystallization time of 24 to 60 hours, preferably 30 to 48 hours. The crystallization equipment is preferably a crystallization kettle. The conditions of the first roasting include: a roasting temperature of 500°C to 550°C, and a roasting time of 3h to 8h. Drying can be performed before roasting. The drying conditions are: a drying temperature of 80°C to 150°C and a time of 3h to 12h.

[0030] According to the present invention, in step (4), the ammonium exchange is a treatment method of immersing the roasted product in an ammonium salt solution. The temperature of the ammonium exchange is 20°C to 90°C, the time is 3h to 6h, and it is repeated 2 to 4 times. The ammonium salt includes one or more of ammonium chloride, ammonium sulfate, ammonium nitrate, ammonium acetate, ammonium oxalate and ammonium phosphate, preferably ammonium nitrate.

[0031] According to the present invention, in step (4), the second roasting conditions include: a roasting temperature of 500°C to 550°C, and a roasting time of 3h to 8h. Drying can be performed before roasting. The drying conditions are: a drying temperature of 80°C to 150°C, and a drying time of 3h to 12h.

[0032] According to the present invention, the relative crystallinity of the MWW structured molecular sieve catalyst relative to the original MWW molecular sieve powder is above 90%, preferably 90% to 100%.

[0033] The third aspect of the present invention provides the use of the above-mentioned MWW structure molecular sieve catalyst or the catalyst prepared by the above-mentioned preparation method in the alkylation reaction of cyclohexene and benzene to synthesize cyclohexylbenzene.

[0034] According to the present invention, the reaction conditions of the application are: reaction temperature of 130-220°C, reaction pressure of 1-4 MPa, molar ratio of benzene to cyclohexene of 1-20, mass space velocity of cyclohexene of 0.2-4 h -1 .

[0035] Compared with the prior art, the advantages of the present invention are as follows:

[0036] 1. The inventors have found that the external specific surface area of ​​the binder-free MWW structured molecular sieve catalyst is 200m 2 / g or more, and the crystal thickness is less than 10nm. When used in the reaction of cyclohexene and benzene alkylation to synthesize cyclohexylbenzene, it not only has good activity, but also can significantly improve the selectivity of cyclohexylbenzene and the catalyst life.

[0037] 2. The inventor has found through research that when preparing a binder-free MWW molecular sieve catalyst in the prior art, it is usually formed by adding a binder to the original powder of the MWW molecular sieve, and then the binder is crystallized into a molecular sieve crystal, which will make the crystal of the crystallization preferentially grow on the surface of the original powder crystal, resulting in the crystal of the molecular sieve catalyst becoming thicker, reducing the surface area, affecting the diffusion performance, and thus affecting its application performance as a catalyst. The inventor has further found that before the crystallization step, the catalyst precursor is pretreated in a mixed solution of cyclohexane and low-carbon alcohols at a certain temperature, and the MWW structured molecular sieve is prone to dehydration condensation of interlayer Si-OH during the calcination process to form a three-dimensional structure. The molecular size of cyclohexane is similar to that of the organic template agent. The introduction of cyclohexane first occupies the gap between the layers of the MWW structured molecular sieve, hindering the organic template agent molecules from entering the molecular sieve interlayer, and inhibiting the superposition between the base layers of the MWW structured molecular sieve during the crystallization process, thereby achieving control of the crystal thickness. At the same time, the separation between layers can increase the specific surface area and expose more active acid sites. By introducing ethanol to control the concentration of cyclohexane, cyclohexane is prevented from excessively entering the molecular sieve pores, hindering the crystallization of the molecular sieve by the organic template, resulting in incomplete crystallization of the MWW structure molecular sieve. In addition, at a certain temperature, ethanol has a pre-crystallization effect on the catalyst precursor, greatly shortening the crystallization time and improving the crystallinity of the catalyst, and finally obtaining a high external specific surface area, ultra-thin layer binder-free MWW structure molecular sieve catalyst.

[0038] 3. The high external specific surface area, ultra-thin layer binder-free MWW structure molecular sieve catalyst of the present invention is used in macromolecular alkylation reactions such as the alkylation of cyclohexene and benzene to synthesize cyclohexylbenzene. It not only has good activity, but also can significantly improve the selectivity of cyclohexylbenzene and the catalyst life. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is the reaction time-cyclohexene conversion curve of Example 1 and Comparative Example 1;

[0040] Figure 2 are X-ray diffraction images of Example 1 and Comparative Example 1;

[0041] Figure 3 is a transmission electron microscope photograph of Example 1Cata-1;

[0042] Figure 4 This is a transmission electron microscope photograph of comparative example 1Cata-1b. DETAILED DESCRIPTION

[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0044] In the present invention, X-ray diffraction (XRD) analysis of the samples was carried out on a Bruker D8 Advanced X-ray diffractometer.

[0045] In the present invention, the molecular sieve crystal thickness and transmission electron microscope spectrum are measured using a JEOL-2010F electron microscope produced by JEOL Ltd.

[0046] In the present invention, the N2 adsorption-desorption isotherm was carried out in a Micromeritics ASAP 2010 physical adsorption instrument under vacuum at 300° C. The specific surface area of ​​the sample was calculated using the BET formula.

[0047] In the present invention, the catalyst life of several hours means that the use time of the catalyst when the cyclohexene conversion rate is lower than 80% is recorded as the catalyst life, that is, the catalyst is deactivated.

[0048] In the present invention, the room temperature is 25°C.

[0049] In the present invention, the calculation formulas for the cyclohexene per-pass conversion and the selectivity of cyclohexylbenzene are:

[0050] Cyclohexene conversion rate = (total product - cyclohexene) / total amount of all components of the product × 100%,

[0051] Cyclohexylbenzene selectivity = cyclohexylbenzene / total amount of all components in the product × 100%.

[0052] Example 1

[0053] (1) MWW molecular sieve raw powder is uniformly mixed with silica sol, sodium aluminate, sodium hydroxide, sesbania powder and 2% nitric acid aqueous solution in a mass ratio of 1:6:0.2:0.1:0.01:0.5, wherein the MWW molecular sieve raw powder is calculated on a dry basis, the silica sol is calculated on a SiO2 basis, and the sodium aluminate is calculated on an Al2O3 basis, and then extruded into strips using a four-leaf clover plate, and dried at 120°C, and then cooled to room temperature to obtain an MWW structured molecular sieve catalyst precursor. The properties of the MWW molecular sieve raw powder are as follows: the SiO2 / Al2O3 molar ratio is 30, the specific surface area is 447m 2 / g. The crystal thickness of the MWW molecular sieve raw powder is 8nm.

[0054] (2) adding the catalyst precursor obtained in step (1) to a mixed solution of cyclohexane and ethanol, wherein the mass ratio of the catalyst precursor to cyclohexane and ethanol is 1:0.5:2.5; treating at 60° C. for 3 hours, and then performing solid-liquid separation.

[0055] (3) The solid separated in step (2) is placed in a crystallization kettle with hexamethyleneimine and water in a mass ratio of 1:1.5:2, the crystallization temperature is 150°C, and the crystallization time is 48 hours. The crystallized product is separated into solid and liquid, and the obtained solid is dried at 120°C for 5 hours and calcined at 550°C for 4 hours.

[0056] (4) The calcined product obtained in step (3) was exchanged with an aqueous solution of ammonium chloride in a 30°C water bath at a mass ratio of molecular sieve (dry basis): ammonium chloride: water = 1:1:10 for 1 hour, and centrifuged; the exchange was repeated twice, and the steps were centrifuged, washed with water, dried at 120°C for 5 hours, and calcined at 550°C for 4 hours to obtain a binder-free MWW molecular sieve catalyst, which was recorded as Cata-1.

[0057] The properties of the MWW molecular sieve catalyst Cata-1 are: external specific surface area of ​​203m 2 / g, the crystal thickness is 7nm, and the SiO2 / Al2O3 molar ratio is 33.

[0058] The catalyst test conditions are: reaction temperature of 160°C, reaction pressure of 3 MPa, molar ratio of benzene to cyclohexene of 10, mass space velocity of cyclohexene of 2 h -1 The test results are shown in Table 2.

[0059] Example 2

[0060] Compared with the catalyst preparation method of Example 1, the difference of Example 2 is that the catalyst precursor obtained in step (1) is added to a mixed solution of cyclohexane and ethanol in a mass ratio of 1:1:3; the mixture is treated at 80°C for 1 hour and then separated. The molecular sieve catalyst finally obtained is recorded as Cata-2.

[0061] The properties of the MWW molecular sieve catalyst Cata-2 are: external specific surface area of ​​239m 2 / g, the crystal thickness is 5nm, and the SiO2 / Al2O3 molar ratio is 33.

[0062] The catalyst test conditions were the same as in Example 1. The test results are shown in Table 2.

[0063] Example 3

[0064] (1) MWW molecular sieve raw powder is uniformly mixed with silica sol, aluminum sulfate, sodium hydroxide, sesbania powder and 4% nitric acid aqueous solution in a mass ratio of 1:4:0.1:0.08:0.02:0.5, wherein the MWW molecular sieve raw powder is calculated on a dry basis, the silica sol is calculated on a SiO2 basis, and the aluminum sulfate is calculated on an Al2O3 basis, and then extruded into strips using a four-leaf clover plate, and dried at 100°C, and then cooled to room temperature to obtain an MWW structure molecular sieve catalyst precursor. The properties of the MWW molecular sieve raw powder are as follows: the SiO2 / Al2O3 molar ratio is 40, the specific surface area is 463m 2 / g. The crystal thickness of the MWW molecular sieve raw powder is 7nm.

[0065] (2) adding the catalyst precursor obtained in step (1) to a mixed solution of cyclohexane and isopropanol, wherein the mass ratio of the catalyst precursor to cyclohexane and ethanol is 1:0.8:3; treating at 50° C. for 3 hours, and then performing solid-liquid separation.

[0066] (3) The solid separated in step (2) is placed in a crystallization kettle with hexamethyleneimine and water in a mass ratio of 1:1.5:2, the crystallization temperature is 160°C, and the crystallization time is 48 hours. The crystallized product is separated into solid and liquid, and the obtained solid is dried at 100°C for 5 hours and calcined at 550°C for 4 hours.

[0067] (4) The calcined product obtained in step (3) was exchanged with an aqueous solution of ammonium chloride in a 50°C water bath for 1 hour at a mass ratio of molecular sieve (dry basis): ammonium chloride: water = 1:1:10, and centrifuged; the exchange was repeated twice, centrifuged, washed with water, dried at 120°C for 5 hours, and calcined at 550°C for 4 hours to obtain a binder-free MWW molecular sieve catalyst, recorded as Cata-3.

[0068] The properties of the MWW molecular sieve catalyst Cata-3 are: external specific surface area of ​​221m 2 / g, the crystal thickness is 7nm, and the SiO2 / Al2O3 molar ratio is 38.

[0069] The catalyst test conditions were the same as in Example 1. The test results are shown in Table 2.

[0070] Example 4

[0071] Compared with the catalyst preparation method of Example 3, the difference of Example 4 is that in step (1), the mass ratio of MWW molecular sieve raw powder to silica sol, aluminum sulfate, sodium hydroxide, sesbania powder and 4% nitric acid aqueous solution is changed to 1:8:0.2:0.08:0.02:0.5, and the molecular sieve catalyst finally obtained is recorded as Cata-4.

[0072] The properties of the MWW molecular sieve catalyst Cata-4 are: external specific surface area of ​​236m 2 / g, the crystal thickness is 7nm, and the SiO2 / Al2O3 molar ratio is 42.

[0073] The catalyst test conditions were the same as in Example 1. The test results are shown in Table 2.

[0074] Example 5

[0075] Compared with the catalyst preparation method of Example 3, the difference of Example 5 is that the properties of the MWW molecular sieve raw powder in step (1) are: SiO2 / Al2O3 molar ratio is 80, specific surface area is 488m 2 / g. The crystal thickness of the MWW molecular sieve raw powder is 8nm, and the molecular sieve catalyst finally obtained is recorded as Cata-5.

[0076] The properties of the MWW molecular sieve catalyst Cata-5 are: external specific surface area of ​​216m 2 / g, the crystal thickness is 7nm, and the SiO2 / Al2O3 molar ratio is 52.

[0077] The catalyst test conditions were the same as in Example 1. The test results are shown in Table 2.

[0078] Comparative Example 1

[0079] Compared with the catalyst preparation method of Example 1, the difference of Comparative Example 1 is that step (2) is omitted. The obtained catalyst is recorded as Cata-1b.

[0080] The properties of the MWW molecular sieve catalyst Cata-1b are: external specific surface area of ​​127m 2 / g, the crystal thickness is 20nm, and the SiO2 / Al2O3 molar ratio is 33.

[0081] The test was performed under the same conditions as in Example 1, and the evaluation results are shown in Table 2.

[0082] Comparative Example 2

[0083] According to the method of Example 1 of CN 111099621B, an MWW structured ultrathin nanosheet molecular sieve Cata-2b was prepared.

[0084] The properties of the MWW molecular sieve catalyst are: the surface area is 186m 2 / g, the crystal thickness is 6nm and the molar ratio is 35.

[0085] The test was performed under the same conditions as in Example 1, and the evaluation results are shown in Table 2.

[0086] Comparative Example 3

[0087] Compared with the catalyst preparation method of Example 1, the difference of Comparative Example 3 is that only cyclohexane is added in step (2) without adding ethanol. The obtained catalyst is recorded as Cata-3b.

[0088] The properties of the MWW molecular sieve catalyst Cata-3b are: external specific surface area of ​​173m 2 / g, the crystal thickness is 7nm, and the SiO2 / Al2O3 molar ratio is 33.

[0089] The test was performed under the same conditions as in Example 1, and the evaluation results are shown in Table 2.

[0090] Table 1 Nitrogen adsorption and desorption characterization data of various catalysts

[0091]

[0092] Note: In Table 1, S BET Refers to the total specific surface area, S external Refers to the external specific surface area, V total is the total pore volume, V micro It refers to the micropore volume.

[0093] Table 2 Evaluation results of catalysts of various examples

[0094]

[0095]

Claims

1. A binder-free MWW structured molecular sieve catalyst, wherein the catalyst has an external specific surface area of ​​200 m 2 / g or more, preferably 200 to 280 m 2 / g, the crystal thickness of the catalyst is less than 10nm, preferably 3-8nm.

2. The catalyst according to claim 1, characterized in that The SiO2 / Al2O3 molar ratio of the binder-free MWW structured molecular sieve catalyst is 20-80.

3. The catalyst according to claim 1, characterized in that The specific surface area of ​​the binder-free MWW structured molecular sieve catalyst is 400 to 600 m 2 / g.

4. The method for preparing the MWW structured molecular sieve catalyst according to any one of claims 1 to 3, comprising: (1) Mixing MWW molecular sieve raw powder, a binder, and an alkali source to obtain a precursor; (2) mixing the precursor of step (1) with cyclohexane and low-carbon alcohol, and separating them; (3) mixing the solid separated in step (2) with a template and water, hydrothermally crystallizing the mixture, and performing a first calcination; (4) subjecting the calcined product obtained in step (3) to ammonium exchange and a second calcination to obtain the MWW structured molecular sieve catalyst.

5. The preparation method according to claim 4, characterized in that: In step (1), the properties of the MWW molecular sieve raw powder are: SiO2 / Al2O3 molar ratio is 25-100, specific surface area is 350-550m 2 / g, the crystal thickness of the MWW molecular sieve raw powder is less than 15nm, preferably 3-10nm.

6. The preparation method according to claim 4, characterized in that: In step (1), in step (1), the binder includes a silicon-containing binder and an aluminum-containing binder; the silicon-containing binder preferably includes at least one of silica sol, white carbon black and silicon powder; the aluminum-containing binder is an inorganic aluminum salt, and the aluminum-containing binder preferably includes at least one of sodium aluminate, aluminum sulfate and aluminum nitrate; And / or, in step (1), the alkali source is a base having an alkali metal and / or an alkaline earth metal as a cation; preferably, the alkali source comprises at least one of sodium hydroxide, potassium hydroxide and barium hydroxide; And / or, in step (3), the template comprises at least one of hexamethyleneimine, piperidine, cyclohexylamine, aniline and homopiperazine.

7. The preparation method according to claim 4, characterized in that: In step (1), the mass ratio of the MWW molecular sieve raw powder, the binder, and the alkali source is 1:0.5-12:0.02-0.2, preferably 1:1-9:0.05-0.1; wherein the MWW molecular sieve raw powder is calculated on a dry basis of the MWW molecular sieve, and the binder is calculated on an oxide basis; And / or, in step (3), the mass ratio of the solid separated in step (2) to the template and water is 1:0.3-1.5:0.5-4, preferably 1:0.8-1.5:1-3.

8. The preparation method according to claim 4, 6 or 7, characterized in that: In step (1), the binder is preferably a silicon-containing binder and an aluminum-containing binder, and the mass ratio of MWW molecular sieve raw powder, silicon-containing binder, aluminum-containing binder and alkali source is 1:0.5~10:0.01~2:0.02~0.2, preferably 1:1~8:0.05~1:0.05~0.1; wherein the MWW molecular sieve raw powder is calculated on a dry basis of MWW molecular sieve, the silicon-containing binder is calculated on a SiO2 basis, and the aluminum-containing binder is calculated on a Al2O3 basis.

9. The preparation method according to claim 4, characterized in that: In step (2), the low-carbon alcohol is selected from at least one of alcohols below C6, preferably at least one of methanol, ethanol, and isopropanol; and / or, in step (2), the mass ratio of the precursor to cyclohexane and low-carbon alcohol is 1:0.5-2:0.5-5; preferably 1:0.7-1.5:1-3; and / or, in step (2), the treatment temperature is 40-90°C and the treatment time is 1-5h.

10. The preparation method according to claim 4, characterized in that: In step (3), the conditions for the hydrothermal crystallization include: a crystallization temperature of 140 to 170°C, preferably 150 to 160°C; a crystallization time of 24 to 60 hours, preferably 30 to 48 hours; and / or, the conditions for the first calcination include: a calcination temperature of 500°C to 550°C, and a calcination time of 3 hours to 8 hours; and / or, the conditions for the second calcination include: a calcination temperature of 500°C to 550°C, and a calcination time of 3 hours to 8 hours.

11. The preparation method according to claim 4, characterized in that: The relative crystallinity of the MWW structured molecular sieve catalyst relative to the original MWW molecular sieve powder is above 90%, preferably 90% to 100%.

12. Use of the MWW structured molecular sieve catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 11 in the alkylation reaction of cyclohexene and benzene to synthesize cyclohexylbenzene.

13. The use according to claim 12, characterized in that: The reaction conditions of the application are: reaction temperature of 130-220° C., reaction pressure of 1-4 MPa, molar ratio of benzene to cyclohexene of 1-20, mass space velocity of cyclohexene of 0.2-4 h -1 .

Citation Information

Patent Citations

  • Method for removing residual silicasol in SAPO-34 molecular sieve product

    CN102319583A

  • Preparation method of binderless MWW structural molecular sieve

    CN107512727A

  • Synthesis method and application of morphology-controllable KL molecular sieve

    CN113860324A

  • Synthetic method of flaky ZSM-11 molecular sieve

    CN115010144A

  • Molecular sieve, preparation method thereof and application of molecular sieve in liquid phase alkylation of benzene and cyclohexene

    CN116265111A